1990
DOI: 10.4315/0362-028x-53.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and Histamine Content in Mahimahi (Coryphaena Hippurus)

Abstract: Decomposition and histamine formation were studied with fresh mahimahi (Coryphaena hippurus) incubated in seawater at 0, 10, 21, and 32°C. The rates of decomposition (loss of quality) and histamine formation both increased at warmer incubation temperatures. Spoilage bacteria were primarily psychrotrophic at 0 and 10°C, while mesophilic bacteria predominated at 21 and 32°C. An increase in pH of the loin tissue was correlated slightly with the histamine level. The correlation between histamine level and loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…Kahawai showed the highest rate of histamine formation and accumulation at 25ЊC, 330 mg/100g muscle within 2 days, followed by 30ЊC (Fletcher et al, 1995). Mahimahi showed the highest histamine accumulation at 32ЊC, reaching 250 mg/100g of fish in 24h, when incubated at 0-32ЊC (Baranowski et al, 1990). Oil-preserved anchovies stored at 20ЊC showed an increased level of histamine, 80 mg/100g, in 2 mo storage, reaching a peak at 300 mg/100g at 7 mo .…”
Section: Scombroid Poisoning Results From Ingestion Of Foodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Kahawai showed the highest rate of histamine formation and accumulation at 25ЊC, 330 mg/100g muscle within 2 days, followed by 30ЊC (Fletcher et al, 1995). Mahimahi showed the highest histamine accumulation at 32ЊC, reaching 250 mg/100g of fish in 24h, when incubated at 0-32ЊC (Baranowski et al, 1990). Oil-preserved anchovies stored at 20ЊC showed an increased level of histamine, 80 mg/100g, in 2 mo storage, reaching a peak at 300 mg/100g at 7 mo .…”
Section: Scombroid Poisoning Results From Ingestion Of Foodsmentioning
confidence: 93%
“…Oil-preserved anchovies stored at 20ЊC showed an increased level of histamine, 80 mg/100g, in 2 mo storage, reaching a peak at 300 mg/100g at 7 mo . At lower temperatures, 0-10ЊC, histamine was formed but at the reduced level mainly by psychrophilic and psychrotrophic histamine-producing bacteria (Baldrati et al, 1980;Frank and Yoshinaga, 1984;Ryser et al, 1984;Morii et al, 1988;Baranowski et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This trend would reflect previous research on tuna that has shown that freezing histamine-producing species negatively impacts the bacteria that produces the histamine decarboxylase that acts on histidine to form histamine (Baranowski and others 1990;Fujii and others 1994;Kim and others 1999). Therefore, the rate of histamine formation and the levels produced are decreased (Baranowski 1990;Kim and others 1999). Histamine levels were drastically reduced when the whole Skipjack tuna was stored on ice ( Figure 4) and remained less than 6.0 ppm for both fresh and frozen/thawed forms.…”
Section: Resultsmentioning
confidence: 95%
“…Both the post-mortem formation of amino acids and their rapid decarboxylation are temperature-dependent (Baranowski et al, 1990). Temperature-abuse potentiates histamine formation in fresh fish (Coryphaena hippurus) at 32 °C is reportedly increasing from 1.6 to 2,920 ppm in 24 h. High histamine formers producing >1,000 ppm histamine were mostly isolated from fish stored at 15-25°C (Kim et al, 2000).The present experiment revealed that there was an increasing trend of histamine production within 24 h of exposure and significant amount of histamine was also increased with increasing time and temperatures (Table 1-4).…”
Section: Resultsmentioning
confidence: 99%